Cover Feature: Five‐Step Enantioselective Synthesis of Islatravir via Asymmetric Ketone Alkynylation and an Ozonolysis Cascade (Chem. Eur. J. 62/2020). Issue 62 (1st October 2020) - Patel, Niki R.; Huffman, Mark A.; Wang, Xiao; Ding, Bangwei; McLaughlin, Mark; Newman, Justin A.; Andreani, Teresa; Maloney, Kevin M.; Johnson, Heather C.; Whittaker, Aaron M.
Abstract : A ball‐and‐stick Houk‐style view of islatravir, the target of the total synthesis described in this work, is depicted in the cover image. Islatravir is on top of a "caged" Human Immunodeficiency Virus to indicate that the molecule is an HIV translocation‐transcriptase inhibitor. In the center of the picture is a circle showing the three key catalytic steps of the synthesis; a biocatalytic cascade, an enantioselective alkynylation, and an ozonolysis deprotection cascade. More information can be found in the Full Paper by H. C. Johnson, A. M. Whittaker, et al. on page 14118 .